PENGARUH DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DINAS PERIKANAN KABUPATEN LAMPUNG UTARA - Dina Ariska Asmara (SIMPLEX: Journal of Economic Management, 2020)
The aim of this research were to determine the Effect of Work Discipline and Employee Competence on Employee Performance. This type of research using quantitative approaches and data collection techniques using questionnaires and observations. The population in this study were employees who worked at Fisheries Service North Lampung Regency and were sampled by purposive sampling using the Slovin formula to 40 respondents. Data analysis using multiple linear regression analysis with the help of SPSS 21. Findings signify that: (1) Is work discipline significant to employee performance? (2) is competence significant for employee performance? (3) Does discipline and competence have a significant effect on employee performance